Analysis Of Consumer Preferences Towards Rendang Products In Padang City Gift Shops - Septiandi, Audilla; Kasmita, Kasmita; Elida, Elida; Gusnita, Wiwik (Universitas Negeri Padang, 2024)
This research is motivated by the lack of predictions about the level of sales of randang products in gift shops, resulting in products that take a long time to sell and reduce product quality. There is a decrease in consumers shopping at certain times. This research aims to describe consumer preferences for randang products in souvenir shops in the city of Padang. This type of research is descriptive with quantitative data. The sampling technique in this research was Proportional Random Sampling which came from 3 souvenir shops in the city of Padang. The selection of respondents was carried out randomly, namely those who had shopped at the souvenir shop amounting to 100 respondents. Data collection for this research was carried out by distributing questionnaires designed based on a Likert scale. The results of the research show that consumer preferences for randang products in souvenir shops in the city of Padang show a respondent achievement level of 86% in the very high category. In terms of price indicators, respondents said that the prices offered were very affordable. The consumer service indicator said it was very good at serving. Finally, in the taste indicator, respondents said that the taste of each souvenir shop was very delicious and had its own characteristics.